DIGITAL SQ3R MODEL: INOVASI STRATEGI MEMBACA PEMAHAMAN BERBASIS LITERASI DIGITAL DI MADRASAH - Muhammad Mushfi El Iq Bali; Putri Awalinda Salsabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology in the era of the 4.0 industrial revolution requires relevant learning strategies to improve the reading literacy of elementary school students, especially in madrasah ibtida'iyah. This study aims to determine the effectiveness of the Digital SQ3R Model in improving the reading comprehension skills of students at Nurul Mun'im Madrasah Ibtida'iyah. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The Digital SQ3R was implemented through the stages of survey, question, read, recite, and review with the support of digital media in the form of videos, interactive quizzes, and reading texts. The results showed an increase in students' quiz scores from the first to the fourth meeting, indicating a gradual improvement in reading comprehension skills. Students also showed higher interest in learning and were actively involved in the learning process. These findings confirm that the Digital SQ3R Model is effective in helping students understand reading content, foster interest in reading, and practice critical thinking skills. Thus, this model can be used as an innovative learning strategy relevant to the characteristics of Madrasah Ibtida'iyah students in the digital era.